Dinamika Pengasuhan Anak Usia Dini: Isu-isu dan Solusinya - Agustiarini Eka Dheasari (Jurnal Kajian Anak (J-Sanak), 2024)
This research has a background in parenting problems carried out by parents in the family. Habits of parents, fathers and mothers, parenting patterns of working parents, parenting by grandparents in guiding, nurturing and leading children in the family. The aim of this research is to determine the characteristics and parenting patterns carried out by parents in various situations in early childhood. The research method used is a literature review method which is carried out by collecting and reviewing scientific sources. Articles taken from 2019-2023 with the help of printed books, Google Scholar, Science Direct and APA. The results of the analysis show that parents' parenting patterns are influenced by various factors such as parental habits, customs, early marriage, and so on. This has a direct impact on the characteristics and personality formation of children.